Computational Insights into the Antioxidant Activity of Luteolin: Density Functional Theory Analysis and Docking in Cytochrome P450 17A1 - Antônio Sérgio Nakao de Aguiar; Lucas Barbosa Ribeiro de Carvalho; Clayson Moura Gomes; Murillo Moraes Castro; Frederico Severino Martins; Leonardo Luiz Borges (Pharmaceuticals)
Background: Luteolin, a flavonoid with well-documented antioxidant properties, has garnered significant attention for its potential therapeutic effects. Objectives: This study aims to investigate the antioxidant properties of luteolin under the influence of solvents, utilizing computational techniques to elucidate its interactions and its potential role as a modulator of enzymatic activities, particularly with Cytochrome 17A1. Methods: Density Functional Theory (DFT) calculations were employed to determine luteolin’s electronic and structural characteristics. Key aspects analyzed included electron density distribution and the energies of the frontier molecular orbitals (HOMO and LUMO). Free radical scavenging mechanisms were explored by comparing the dissociation enthalpy of the O–H bond in the absence and presence of water molecules. Additionally, molecular docking simulations were performed to assess the interactions of luteolin with Cytochrome 17A1, identifying preferred binding sites and interaction energies. Results: The findings indicate that luteolin possesses distinct structural and electronic features that contribute to its effectiveness in protecting against oxidative stress. However, hydrogen bonding interactions with water molecules were found to influence the dissociation enthalpy of the O–H bond. Docking simulations revealed significant interaction profiles between luteolin and Cytochrome 17A1, suggesting its potential role as a modulator of this protein. Conclusions: This study underscores the therapeutic potential of luteolin and highlights the importance of computational techniques in predicting and understanding the molecular interactions of bioactive compounds with biological targets. The results provide valuable insights that may aid in developing new therapeutic strategies for diseases associated with oxidative stress.